Conceptual Model of Smart Tailor Architecture for Garment Industry - Rohaya Dahari; Haslina Mohd; Nor Iadah Yusop; Zahurin Mat Aji (International Journal of Supply Chain Management, 2018)
Smart Tailor is an architecture that integrates various stakeholders such as tailors, designers, and customers in a garment industry. The architecture provides the ability to promote, manage and fulfill supply and demands of their product via electronic ways. Currently, the implementation of the related transaction processes is done manually which may cause time consuming and inefficiency in fulfilling the supply and demands of the garment products. Therefore, this paper aims to construct a conceptual model of Smart Tailor Architecture. This study adopted the first phase of the Rational Unified Process approach, Inception, by identifying the goal of the conceptual model and the verified requirements of the Smart Tailor architecture. Then, the verified requirements were transformed into the Smart Tailor components using the Unified Modeling Language approach. Finally, the verified components by experts become a conceptual model of the Smart Tailor Architecture. The model may contribute to the garment industry stakeholders as well as researchers, decision makers, and software developers.